In-silico studies to recognize repurposing therapeutics toward arginase-I inhibitors as a potential onco-immunomodulators - Zaki, Magdi E. A.; Al-Hussain, Sami A.; Al-Mutairi, Aamal A.; Samad, Abdul; Ghosh, Arabinda; Chaudhari, Somdatta; Khatale, Pravin N.; Ajmire, Prashant; Jawarkar, Rahul D. (Frontiers in Pharmacology, 2023)
Rudolf Virchow related cancer to immunological function. Tumors have leukocytes. ARG1 and iNOS-expressing MDSCs and TAMs deplete intracellular and extracellular arginine. TCR signalling slows and cells produce ROS and RNS, aggravating the situation. Human arginase I, a double-stranded manganese metalloenzyme, degrades L-arginine into L-ornithine and urea. Hence, a QSAR was conducted to uncover arginase-I inhibition's unidentified structural components. A balanced QSAR model with strong prediction performance and clear mechanistic interpretation was created using 149 compounds from various structural scaffolds and compositions. R2tr, Q2LMO, and R2ex surpass OECD standards. This QSAR study linked arginase-I inhibition to lipophilic atoms' proximity to the molecule's centre of mass (within 3A), the donor's distance from the ring nitrogen (3 bonds), and the surface area ratio. We used 1650 FDA compounds from the zinc database for a QSAR-based virtual screening of the only arginase-I inhibitors under development, OAT-1746 and two more. 112 potential hit compounds have arginase-I receptor PIC50s below 10 nm. QSAR-based virtual screening was used to evaluate the QSAR model's applicability domain in respect to the most active hit compounds. The top hit molecule, ZINC000252286875, has a leverage value of HAT i/i h* = 0.140, which is acceptable according to the Williams plot. One of 112 arginase-I molecular docking hit compounds had a docking score of -10.891 kcal/mol (PIC50 = 10.023 M). ZINC000252286875-linked arginase-1 had 2.9 RMSD and non-protonated 1.8. Stable ZINC000252286875-bound protein RMSD plots. Protonated-ZINC000252286875-bound proteins are 25 Rg. Compact 25.2-Rg non-protonated protein-ligand. Protonated and non-protonated ZINC000252286875 stabilised protein targets in binding cavities postmortem. Both protonated and unprotonated arginase-1 protein residues displayed substantial root mean square fluctuations (RMSF) lasting 500 ns. Protonated and non-protonated ligands interacted with proteins throughout the simulation. ZINC000252286875 bound Lys64, Asp124, Ala171, Arg222, Asp232, and Gly250. Residue 232 was 200% ionic. 500-ns-simulated ions. Salt-bridged ZINC000252286875 docked. ZINC000252286875 ionised Lys68, Asp117, His126, Ala171, Lys224, and Asp232 residues. Asp117, His126, and Lys224 interacted 200% ionically. GbindvdW, GbindLipo, and GbindCoulomb energies affected protonation and deprotonation. ADMET drugs include ZINC000252286875. Hence, nanomolar dosages of a novel, potent arginase-I inhibitor were identified. This research may lead to immune-modulating cancer therapy arginase I inhibitors.